Efficacy of Subconjunctival Bevacizumab Injections before and after Surgical Excision in Preventing Pterygium Recurrence - Raffaele Nuzzi; Federico Tridico (Journal of Ophthalmology)
Purpose. To evaluate the efficacy of subconjunctival bevacizumab injections, before and after surgical excision with bare sclera technique, in preventing postoperative pterygium recurrence. Material and Methods. 83 eyes of 83 patients affected with primary pterygia underwent surgical excision. 42 eyes received two subconjunctival bevacizumab injections, at the dosage of 2.5 mg/0.1 ml, one week prior surgery and one week after intervention. Recurrence rate was evaluated among the two groups. Moreover, modifications of pterygium size and grade one week after the first injection were evaluated. Results. At 6 months after surgery, the recurrence rate was 7.14% in the bevacizumab group and 24.39% in the control group. Significant changes of pterygium size and grade were reported after the first injection. No important complications related to bevacizumab subconjunctival injections were registered. Conclusions. The application of subconjunctival bevacizumab injections, at the dosage of 2.5 mg/0.1 ml, before and after surgical pterygium excision, may be useful in preventing lesion recurrence after bare scleral procedures. Furthermore, bevacizumab subconjunctival administration is well tolerated and may represent a safer alternative if compared with other surgical techniques and adjunctive drugs. This trial is retrospectively registered with ISRCTN Registry on 18 April 2017, TRN: ISRCTN11424742.